Do Investors Suffer from Money Illusion? A Direct Test of the Modigliani–Cohn Hypothesis - Acker, Daniella; Duck, Nigel W. (Review of Finance, 2013)
Abstract We propose a direct test of the explanation by Modigliani and Cohn (MC) for the positive correlation between inflation and equity values—that it results from investors’ money illusion. This explanation, unlike its main rivals, suggests that because in inflationary periods dividends will, on average, be higher than expected, dividend announcements will trigger positive abnormal returns. These will be higher the higher the inflation, and the more levered the firm. The behavior of abnormal returns of US stocks on dividend-announcement days from 1955 to 2007 supports these predictions. We investigate alternative explanations of our results. None dominates MC’s.